Removal efficacy of fly ash composite filler on tailwater nitrogen and phosphorus and its application in constructed wetlands - Wang, Shuhang; Yang, Haoran; Che, Feifei; Huang, Wei; Yang, Dianhai (Frontiers in Chemistry, 2023)
Constructed wetlands (CWs) have been widely used in tailwater treatment. However, it is difficult to achieve considerable removal efficiency of nitrogen and phosphorus in tailwater solely by CWs—an efficient green wetland filler is also important. This study investigated 160 domestic sewage treatment facilities (DSTFs) in rural areas from two urban areas in Jiaxing for TP and NH3-N and found that TP and NH3-N concentrations in rural domestic sewage (RDS) in this plain river network are still high. Therefore, we selected a new synthetic filler (FA-SFe) to enhance nitrogen and phosphorus reduction, and we discuss the importance of filler in constructed wetlands. Experiments revealed the adsorption capacity of the new filler: the maximum adsorption amounts of TP and NH3-N reached 0.47 g m-2 d-1 and 0.91 g m-2 d-1, respectively. The application potential of FA-SFe was verified in actual wastewater treatment, with the removal rates of ammonia nitrogen and TP reaching 71.3% and 62.7%, respectively. This study provides a promising pathway for nitrogen and phosphorus removal from rural tailwaters.